Administration of Smolensk during the siege in years 1609–1611 - Kupchenko, Konstantin; Nikitina, Natalya (City and War, 2021)
The present article deals with poorly researched questions of the functioning of the administrative bodies of Smolensk during the defence period 1609–1611. The work on the basis of current sources and contemporary historiography deals with the management of the Smolensk period. The relevance of the project stems from the very limited knowledge of day-to-day management issues, which have not been reflected in both ad hoc and comprehensive studies of the history of the region during the Dark Time period. The work is based on strict adherence to the principle of historism. The article uses the most scientific and productive methodological guidelines of modern historical research directions. The integrated approach of the study involves the following methods: historical description, historical analysis, comparative, micro-history. The whole complex of archival heuristics tools is used in working with the documentary material. The authors investigate whether there were any changes in the structure of city administration at that time and which authorities in the defense period exercised authority over the population of Smolensk. The powers, competence and practical activities of the voivodeship administration and the civil administration (Zemstvo, Posad) have been examined. The authors conclude that the entire authority in the city was in the hands of the voivodes. It was from them that all orders and orders on organization of the Smolensk army, strengthening of defense capability and regulation of siege life were issued. But at the same time, it is noted that during the siege of 1609–1611. In Smolensk, a peculiar corporation of military and civilian administrative authorities has been formed to coordinate common efforts for the defence of the city.